Anesthetic challenges in managing a case of type III laryngo-tracheo-esophageal cleft - Nisha Rajmohan; Hassy Prakasam; Johny V Francis (Wolters Kluwer Medknow Publications, 2012)
Laryngo-tracheo-esophageal cleft (LTEC) is a rare congenital anomaly characterized by failure of fusion of the cricoid cartilage posteriorly and incomplete development of the tracheo-esophageal septum. Securing the airway during anesthesia in patients with LTEC, especially in the severe forms is a challenge. We describe the anesthetic management and the airway challenges in a neonate with type III LTEC who underwent bronchoscopy and repair of LTEC.